ESENSI KARYA DIAKONIA GEREJA MENURUT YOHANES 6:1-15 - Kartijo, Fransiskus Nala (Lembaga Penelitian STKIP Widya Yuwana, 2025)
This article aims to explore the essence of diaconal ministry, which constitutes a crucial dimension of church life. The attitudes and actions demonstrated by Jesus in the account of the multiplication of bread in John 6:1-15 provide insightful inspiration for how the church can embody diaconal ministry. In the sign of the multiplication of bread, Jesus not only takes the initiative to feed the multitude following Him, but also acts as a servant, distributing the bread of life to them, and at the same time, He transforms them into a new community in Him. An analysis of Jesus’ actions reveals that the church’s diaconal ministry must begin with attentiveness to people’s needs, followed by gathering, feeding (Word and Eucharist), and transforming them. To uncover the depth of this message, this study employs a synchronic analysis using actantial schemes and examines the characteristics of Jesus’ actions toward the crowd during the multiplication of bread. Through a narrative analysis of John 6:1-15, several theological insights will be drawn for a contextual approach to diaconal ministry.